Donor Hepatectomy and Implantation Time Are Associated With Early Complications After Liver Transplantation: A Single-center Retrospective Study. Issue 5 (28th May 2020) - Gilbo, Nicholas; Fieuws, Steffen; Meurisse, Nicolas; Nevens, Frederik; van der Merwe, Schalk; Laleman, Wim; Verslype, Chris; Cassiman, David; van Malenstein, Hannah; Roskams, Tania; Sainz-Barriga, Mauricio; Pirenne, Jacques; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Donor hepatectomy and liver implantation time reduce long-term graft and patient survival after liver transplantation. It is not known whether these surgical times influence early outcomes after liver transplantation. Methods: This single-center study evaluated the effect of donor hepatectomy and implantation time on the risk of nonanastomotic biliary strictures (NAS) occurring within 1 year and of early allograft dysfunction (EAD) after deceased-donor solitary liver transplantation, adjusting for other donors, recipient, and surgical factors. Results: Of 917 transplants performed between January 2000 and December 2016, 106 (11.56%) developed NAS and 247 (27%) developed EAD. Donor hepatectomy time (median 35 min, IQR: 26–46) was an independent risk factor of NAS [adjusted hazard ratio, 1.19; 95% CI, 1.04-1.35; P = 0.01]. Implantation time (median 80 min, IQR: 69–95) was independently associated with EAD [adjusted odds ratio (OR), 1.15; 95% CI, 1.07-1.23; P < 0.0001). The risk of EAD was increased by anastomosis time of both portal vein (adjusted OR, 1.26; 95% CI, 1.12-14.42; P = 0.0001) and hepatic artery (adjusted OR, 1.13; 95% CI, 1.04-1.22; P = 0.005). The magnitude of these effects was similar in donation after circulatory death liver grafts. Conclusions: Donor hepatectomy and implantation time negatively affect short-term outcomes.